Eka Learning Center (ELC) Tutoring Assistance thru the Development of SOPs and a Transparent Bookkeeping System Based on Excel Software - Anora, Ayu; Multazam, Muhammad; Mardhiah, Ainol; Muktarullah, Millatina; Ningsih, Eka Utami; Yusnidar; Aulia, Muhammad Kahfi (Unram Journal of Community Service, 2025)
Non-formal educational institutions such as tutoring centers play a vital role in enhancing the quality of education within communities. However, many of these institutions face challenges in management governance, particularly in establishing standardized operational procedures and financial accountability systems. This community engagement program aimed to strengthen the management capacity of the Eka Learning Center (ELC) by developing Standard Operating Procedures (SOPs) and an accountable, transparent bookkeeping system using Microsoft Excel. The method adopted was a participatory approach, consisting of socialization sessions, technical training, simulation practices, and intensive mentoring for ELC administrators. The outcomes demonstrated a significant improvement in the partners’ understanding and skills in preparing applicable SOP documents and recording financial transactions systematically through customized Excel templates. Furthermore, the partners showed enhanced capacity in generating basic financial reports that are internally and externally accountable. This program contributed positively to increasing operational efficiency and institutional transparency. The success of this activity is expected to serve as a model for similar educational institutions and support the achievement of Sustainable Development Goals (SDGs), particularly in the areas of quality education and good institutional governance.